Plínio Corrêa de Oliveira: pensamento católico e ação política na era Vargas (1930-1945) - Alencar Júnior, Moacir Pereira (2014)
The 1930s represented a new phase in the history of Brazil. The Revolution of 1930 ended the First Republic, which lasted for exactly 41 years (1889- 1930). Deserves to be emphasized the international environment of the period, where a severe economic crisis shakes the U.S. and European countries, raising questions about the functionality of democratic institutions, increasing emergence of strong states, guided by a more interventionist stance, whether in the social structure as in economics. Within this perspective, in Brazil, the new ruling elites linked to Getúlio Vargas, govern the country in the midst of a lot of events. In Brazil, we have witnessed an era of true boiling doctrinal ideologies and actions moving the national intelligentsia. The country witnessing the rise of various movements: political, Catholics, social, etc. At this time the rise of PCB (Brazilian Communist Party), the rise of AIB (Brazilian Integralist Action), as well as the consolidation of LEC (Catholic Electoral League) occurs. The Catholic movement, represented by different intellectual figures, maintains an eminently conservative and traditionalist wing, which will see its skyline early signs and protests to come to originate in the country - with more force, from the second half of the 1940s - the progressive and modernist Catholicism, inspired by the integral humanism. One of the major intellectual figures of the period representing the state of São Paulo is Plínio Corrêa de Oliveira. Lawyer and devout Catholic, and son of a family of royalist and ultramontane training, he represents through his thought and political action the Catholic conservative strand. Thus, the goal of this dissertation is to analyze the trajectory of Plínio Corrêa de Oliveira in this context. Thought and action, as a Catholic leader and political leader in the Catholic Electoral League and later as Deputy Constituency, as well as your performance in the journal 'O Legionário' and also as President of the Archdiocesan Board of Catholic Action of the State of São Paulo. To carry out this work will be analyzed his articles published in newspapers, in addition to his books, speeches and interviews.